The Psychosocial Value of Employment : Evidence from a Refugee Camp - Hussam, Reshmaan (World Bank, Washington, DC, 2022)
Employment may be important to well-being for reasons beyond its role as an income source. This paper presents a causal estimate of the psychosocial value of employment in refugee camps in Bangladesh. The study involves 745 individuals in a field experiment with three arms: a control arm, a weekly cash arm, and an employment arm of equal value. The findings show that employment raises psychosocial well-being substantially more than cash alone, and 66 percent of the employed are willing to forego cash payments to continue working temporarily for free. Despite material poverty, the individuals in the sample both experience and recognize the nonmonetary, psychosocial value of employment.